Estudo teórico de antissítios e impureza substitucional de oxigênio em nanofio de SiC - Rosso, Eduardo Fuzer (2010)
In this work first we perform a study about the stability, and the electronic properties of SiC growth in the [111] direction when defects are present. We use the supercell method and the dangling bonds on the surface of the nanowire are saturated using hydrogen atoms. We also study antisites and substitutional oxygen impurity in this nanowire. For this study, we perform total energy and band structure calculations in order to find the most stable positions for the defects and the influence of defects on the electronic properties. The first principles calculations are based in the density functional theory (DFT). The Generalized Gradient Approximation (GGA) is used for the exchange-correlation term and the ion-electron interactions are replaced by norm-conserving fully separable Troullier-Martins pseudopotentials. For the calculations we use the SIESTA-code and the standard Kohn-Shan (KS) equations are solved in a fully selfconsistent way. The Khon-Sham orbitals are expanded using a linear combination of numerical pseudo-atomic orbitals (PAOs). All calculations use a split-valence double-zeta quality basis set enhanced with a polarization function. Our results show that the most stable antisite is a carbon atom occupying a silicon site (CSi). The substitutional oxygen impurity is most stable in a carbon site (OC). Both defects present a greater stability in the surface of the nanowire when compared with the core of the nanowire. The analysis of electronic structure of bands shows that these defects give rise to electronic levels localized in the band gap of the nanowire. Keywords: density functional theory; SiC nanowires, antisites, impurity.